The Development and Application of an Online Malay Language Corpus-Based Lexical Database - Lay Wah Lee; Hui Min Low (Kajian Malaysia, 2014)
The Online Malay Language Corpus-based Lexical Database for Primary Schools discussed in this paper is a long-term research project by the School of Educational Studies, Universiti Sains Malaysia. Based on a corpus of Malay language textbooks used in primary schools, the project aims to develop a lexical database of Malay words commonly encountered by elementary school children in Malaysia. Available online, the database has an interactive interface that allows users to search in real-time primary linguistic features such as word frequency, word length, phoneme length, number and type of syllables, as well as word category. The database has proven to be a useful resource for both researchers and practitioners who use it to identify linguistically and culturally appropriate sets of word stimuli for material development, language assessment, language teaching, and language remediation. These applications facilitate and promote evidence-based teaching and research practices pertaining to reading acquisition in the Malay language. The system has undergone initial validation and is continuously being revised and expanded to improve on its usability, readability, and accuracy.